Developing and Psychometrically Testing the Functions of Diabetes Peer Support Group Scale. Issue 4 (December 2016) - Chiou, Chii-Jun; Huang, Hsiao-Ling; Lin, Ying-Chun; Wang, Ruey-Hsia
ABSTRACT: Background: Peer support groups for people with diabetes are increasingly considered a part of the healthcare system. Understanding the functions of peer support groups assist healthcare professionals to provide critical assistance. Purpose: The purpose of this study was to develop and assess the psychometric properties of the Functions of Diabetes Peer Support Group (F-DPSG) scale. Methods: This study used a cross-sectional design. A 16-item F-DPSG scale was developed and administered to 589 patients with Type 2 diabetes who were selected from 34 diabetes peer support groups in Taiwan. Construct validity was evaluated using exploratory and confirmatory factor analyses and by examining the correlation with the score of the Chinese Diabetes Management Self-Efficacy Scale. Reliability was tested using internal consistency and test–retest reliability. Results: The 16-item F-DPSG scale, including four subscales, was supported by a second-order confirmatory factor analysis, with the following fit indices: χ 2 / df ratio = 2.60, comparative fit index = .94, normed fit index = .91, and root mean square error of approximation = .07. The four subscales were "enhancing self-care practice, " "obtaining knowledge and skills, " "psychological support, " and "collective identification." The score of the F-DPSG scale correlated significantly with the score of the Chinese Diabetes Management Self-Efficacy Scale ( r = .45, p < .001). The Cronbach's α and test–retest reliability of the F-DPSG global scale and subscales were all above .70. Conclusions/Implications for Practice: The F-DPSG scale showed satisfactory reliability and validity. Healthcare providers may use the F-DPSG scale to assess the functions of peer support groups for people with diabetes and to provide necessary assistance.